Komunikasi Transendental Ruqyah Syar’iyah sebagai Metode Penyembuhan Alternatif - Eka Sari Yanti; Kusmawati Hatta (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2024)
This research aims to get a bright spot of the Ruqyah Syar’iyah practice method which has been widely chosen as an alternative treatment method. This study uses a qualitative descriptive approach with the literature review method as the main foothold in data collection. The results of the study show that ruqyah syar’iyah includes transcendental communication, namely communication built by a servant with his God. In this communication, there are all the basic elements of communication. The source of communication or communicators consists of God and humans. The message is in the form of Allah's verses through the Qur'an and prayers, dhikr that people convey to Allah and the channel is the Qur'an. The recipient or communicator is basically the same as the source or communicator. The expected effect and feedback in this transcendental communication is the fulfillment of the servant's prayer, inner peace. Ruqyah Syariyah as an alternative medicine method is a practice that is recommended in Islam. The treatment of the ruqyah method can be practiced on all kinds of diseases, both physical, mental and jinn and magic disorders. The guidelines for reading the verses of the Quran and prayers and dhikr that can be applied refer to the verses that have been read by the Prophet contained in the Hadith. In essence, the healing obtained by the ruqyah sharia method is inseparable from the belief in Allah as the supreme source of healing.